Mapping of District-Based Poverty Levels Using Spatial Analysis in Medan City - Feyza Zaki Nandana; Christiani Joice Siallagan; Laura Annisa Purba; Elang Putri Sekar Arum; Brian Hardiwan Gea; Hanna Dewi Marina Hutabarat (Lembaga Riset Mutiara Akbar, 2026)
This study aims to map poverty levels based on sub-districts in the City of Medan using a descriptive quantitative approach and spatial analysis. The data used consists of population numbers, the number of poor people, and poverty percentages in 21 sub-districts in 2023, obtained from the Medan City BPS. Analysis was conducted through descriptive statistics, Natural Breaks (Jenks) classification, and choropleth map visualization. The results of the study show that the average poverty level in Medan City is 10.10% with a clear spatial clustering pattern. Northern areas such as Medan Belawan, Medan Labuhan, Medan Marelan, and Medan Deli have high to very high poverty levels, while central and southern areas tend to be lower. These findings indicate spatial disparities between regions and can serve as a basis for more targeted poverty alleviation policies.